Case report: Can cochlear implant stimulation lead to improved balance even after vestibular neurectomy? - Sluydts, Morgana; De Laet, Chloë; De Coninck, Liesbeth; Blaivie, Catherine; van Dinther, Joost J. S.; Offeciers, Erwin; Wuyts, Floris L.; Zarowski, Andrzej (Frontiers in Neurology, 2023)
Introduction In a previous manuscript from our research group, the concept of vestibular co-stimulation was investigated in adult subjects who received a cochlear implant (CI). Despite what literature reports state, no signs of vestibular co-stimulation could be observed. Results In this case report, it was described how a woman, who previously underwent a neurectomy of the left vestibular nerve and suffers from bilateral vestibulopathy (BVP), reported improved balance whenever her CI on the left was stimulating. Unexpectedly, the sway analyses during posturography indeed showed a clinically relevant improvement when the CI was activated. Discussion Vestibular co-stimulation as a side effect of CI stimulation could not be the explanation in this case due to the ipsilateral vestibular neurectomy. It is more likely that the results can be attributed to the electrically restored auditory input, which serves as an external reference for maintaining balance and spatial orientation. In addition, this patient experienced disturbing tinnitus whenever her CI was deactivated. It is thus plausible that the tinnitus increased her cognitive load, which was already increased because of the BVP, leading to an increased imbalance in the absence of CI stimulation.